Analytical Study on the Behavior of Reinforced Concrete Beams Strengthened with Shape Memory Alloys (SMA) Using the Near-Surface Mounted (NSM) Technique (Latakia University (formerly Tishreen) Journal for Research and Scientific Studies - Engineering Sciences Series, 2025)
In recent years, there has been increasing interest in strengthening Reinforced Concrete (RC) beams using Fiber-Reinforced Polymer (FRP) strips or laminates through the Near-Surface Mounted (NSM) technique. While many studies have confirmed the effectiveness of this method, they have also shown that it leads to a reduction in the ductility of the beams. This research proposes a promising advanced technique for strengthening RC beams using Shape Memory Alloys (SMAs), known as the NSM-SMA technique, which may help address some of the challenges associated with NSM-FRP technique.This analytical study aims to evaluate the effect of the NSM-SMA technique on the ductility behavior of RC beams through numerical analysis using the OpenSEES software. Several widely used types of SMA alloys in civil engineering applications were adopted and compared with the strengthening performance of FRP.The results revealed that the NSM-SMA technique significantly improved beam ductility, with improvements exceeding 90% in some specimens. In contrast, a reduction in ductility was observed when using the NSM-FRP technique, compared to the unstrengthen reference beam.